From 1st condition:
3^(x+1)=81
Take log on both sides,
➡ log [3^(x+1)]=log81
Use the property: log(x^a)=a logx
➡ (x+1) log 3=log(3⁴)
➡ (x+1) log 3=4×log 3
➡ (x+1)=4 (log 3 /log 3)
➡ x+1=4
➡ x=3➡↪➡↪ ANS
From 2nd condition, (Same process are repeated)
81^(x-y)=3
➡ 3^4(x-y)=3
➡ log [3^4(3-y)]=log 3
➡ 4(3-y) log 3=log 3
➡ (3-y)=(log 3)/(4log 3)
➡ 3-y=(1/4)
➡ y=11/4 ➡↪➡↪ ANS
Let's solve your equation step-by-step.<span><span><span>3<span>(<span><span>2x</span>−1</span>)</span></span>+<span>5<span>(<span>x−3</span>)</span></span></span>=<span><span>4x</span>+7</span></span>Step 1: Simplify both sides of the equation.<span><span><span>3<span>(<span><span>2x</span>−1</span>)</span></span>+<span>5<span>(<span>x−3</span>)</span></span></span>=<span><span>4x</span>+7</span></span>Simplify:<span><span><span>11x</span>−18</span>=<span><span>4x</span>+7</span></span>Step 2: Subtract 4x from both sides.<span><span><span><span>11x</span>−18</span>−<span>4x</span></span>=<span><span><span>4x</span>+7</span>−<span>4x</span></span></span><span><span><span>7x</span>−18</span>=7</span>Step 3: Add 18 to both sides.<span><span><span><span>7x</span>−18</span>+18</span>=<span>7+18</span></span><span><span>7x</span>=25</span>Step 4: Divide both sides by 7.<span><span><span>7x</span>7</span>=<span>257</span></span><span>x=<span>257</span></span>Answer:<span>x=<span><span>257
</span>
</span></span>Let's solve your equation step-by-step.<span><span><span>5−x</span>−<span>(<span><span>2x</span>+3</span>)</span></span>=<span>3+<span>8x</span></span></span>Step 1: Simplify both sides of the equation.<span><span><span>5−x</span>−<span>(<span><span>2x</span>+3</span>)</span></span>=<span>3+<span>8x</span></span></span>Simplify:<span><span><span>−<span>3x</span></span>+2</span>=<span><span>8x</span>+3</span></span>Step 2: Subtract 8x from both sides.<span><span><span><span>−<span>3x</span></span>+2</span>−<span>8x</span></span>=<span><span><span>8x</span>+3</span>−<span>8x</span></span></span><span><span><span>−<span>11x</span></span>+2</span>=3</span>Step 3: Subtract 2 from both sides.<span><span><span><span>−<span>11x</span></span>+2</span>−2</span>=<span>3−2</span></span><span><span>−<span>11x</span></span>=1</span>Step 4: Divide both sides by -11.<span><span><span>−<span>11x</span></span><span>−11</span></span>=<span>1<span>−11</span></span></span><span>x=<span><span>−1</span>11</span></span>Answer:<span>x=<span><span>−1</span>11</span></span>
<span>Espero que esto ayude</span>
Answer:
Step-by-step explanation:
−189=4x−3(−4x+15)
−189=16x−45
16x−45=−189
16x−45+45=−189+45
16x=−144
16x
/16
=
−144
/16
x=−9
Good luck honey !!
the answer is $3.88
Step-by-step explanation:
because the ice cream was $4.00 and they subtracted it by 12% which would be $4.00 minus .12 which would give you $3.88